Pediatric Critical Illness Score, Clinical Characteristics and Comprehensive Treatment of Children with Severe Mycoplasma Pneumoniae Pneumonia - Fang, Chengchao; Mao, Yueyan; Jiang, Mingfen; Yin, Wei (Frontiers in Surgery, 2022)
Objective: To investigate the clinical characteristics of children with severe Mycoplasma pneumoniae pneumonia (SMPP) and the correlation with pediatric critical illness score (PICS)and to explore the effect of combined treatment with antibiotics and glucocorticoids. Methods: The medical records of 120 children with SMPP admitted to our hospital from January 2020 to June 2021 were retrospectively analyzed. Children with a PICS score greater than 80 within 24 hours of admission were included in the non-critical group, those with a score of 71-80 were included in the critical group, and those with a score of ≤70 were included in the extremely critical group. The relevant clinical data and examination indicators of the three groups of children were intercepted and compared. The correlation between the clinical characteristics of children with SMPP and PICS was analyzed by univariate analysis and multivariate Logistic regression analysis. According to the different treatment methods, the children were subdivided into the control group (n=54) who received antibiotics alone and the comprehensive group (n=66) who received antibiotics combined with glucocorticoid therapy. Result: Within 24 hours of admission, among the 120 children with SMPP, 79 had a score of >80, 32 had a score of 71-80, and 9 had a score of ≤70. Before discharge, among the 120 SMPP children, 99 had PICS>80, 17 had 71-80, and 4 had ≤70. Univariate analysis showed that there were no significant differences in gender ratio, ratio of fever duration >10 days, age and WBC among the three groups (P>0.05), the differences in the ratio of abnormal ECG, the ratio of ≥2 pathogenic infections, the ratio of ≥2 systemic damages, CRP levels, and D-dimer levels were statistically significant when compared among the three groups (P<0.05). Multivariate Logistic regression analysis showed that the number of Co-systemic damages and the level of D-dimer were negatively correlated with PICS classification (P<0.05). Conclusion: PICS can effectively reflect the clinical characteristics of children with SMPP. The comprehensive treatment effect of azithromycin combined with glucocorticoid is significantly better than that of azithromycin alone. It can effectively reduce the level of inflammation in children with SMPP, improve the immune function of children.